Non-newtonian liquid-gas non-uniform stratified flow with interfacial level gradient through horizontal tubes - Li, Haiwang (2014)
This paper presents the predictions of the axial distribution of liquid level and interfacial level gradient (ILG) for nonuniform non-Newtonian liquid-gas flow in horizontal tubes. The non-Newtonian liquid is described using power-law model, while the model of Heywood and Charles for uniform non-Newtonian liquid-gas two-phase flow, which was developed based on one dimensional energy equation, is extended to describe nonuniform stratified flow by incorporating the effect of interfacial level gradient. Two different critical liquid levels are found from the energy equation and are adopted as boundary condition to calculate the interfacial level distribution upstream of the channel exit. The results from the model are compared with the published numerical and experimental data. The results show that the model can predict the interfacial level distribution and interfacial level gradient for nonuniform stratified flow. Low liquid velocity, low gas velocity and high liquid viscosity are beneficial for forming a nonuniform flow with interfacial level gradient. The difference between the analytical model and the published data is smaller than 10%.